Peran Program Magang MBKM Mahasiswa IAIN Palangka Raya di MIS Fathul Iman: Tanggapan Guru MIS Fathul Iman Palangkaraya - Dinna Aulia Putri Andani; Sulistiyowati Sulistiyowati; Hasanah Hasanah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The MBKM internship program for IAIN Palangka Raya students at MIS Fathul Iman aims to enhance the educational experience and practical teaching skills. This qualitative descriptive study investigates teachers' responses about the internship's impact over four months. Through interviews, the research reveals that teachers perceive the program as beneficial for fostering collaboration, improving student engagement, and enhancing teaching methodologies. Teachers noted that the presence of interns helped alleviate their workload and introduced fresh perspectives in the classroom. Additionally, the program facilitated professional development for both interns and educators, creating a mutually beneficial learning environment. The findings suggest that the MBKM internship program is a valuable initiative that not only contributes to the personal growth of students but also strengthens the educational community. This study underscores the importance of practical training in teacher education and its positive influence on teaching effectiveness and student outcomes.